Multi-platform Process Flow Models and Algorithms for Extraction and Documentation of Digital Forensic Evidence from Mobile Devices - Ocen, Gilbert Gilibrays; Bongomin, Ocident; Mugeni, Gilbert Barasa; Mutua, Stephen Makau; Semwogerere, Twaibu (East African Nature and Science Organization, 2022)
The increasing need for the examination of evidence from mobile and portable gadgets increases the essential need to establish dependable measures for the investigation of these gadgets. Many differences exist while detailing the requirement for the examination of each gadget to help detectives and examiners in guaranteeing that any kind of evidence extracted/ collected from any mobile device is well documented and the outcomes can be repeatable, a reliable and well-documented investigation process must be implemented if the results of the examination are to be repeatable and defensible in courts of law. In this paper, we developed a generic process flow model for the extraction of digital evidence in mobile devices running on Android, Windows, iOS, and Blackberry operating systems. The research adopted a survey approach and extensive literature review as a means to collect data. The models developed were validated through expert opinion. Results of this work can guide solution developers in ensuring the standardization of evidence extraction tools for mobile devices.